Magnetoelectric Speed Sensor to Detect Ultra-Low Frequency Vibrations - Dong Ke; Qian Yuxia; Yuan Zhangyi (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Ultra-low frequency vibrations are ordinary physical phenomena, and absolute vibrant sensors are usually used to detect them. The author presents a method that using magnetoelectric speed sensor to detect ultra-low frequency vibrations. With cascade correcting circuit, the lowest frequency that can be measured will be less than 0.5Hz while the best damping is maintained. The author has systematically analyzed the correcting circuit, transfer function, theory of operation, and the difference between output characteristics before and after correcting to the ultra-low frequency sensor. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2480